Use of Online Health Communities in Smoking Cessation: a Social Support Perspective - Chenglong Li; Hongxiu Li; Reima Suomi (United States, 2022)
Online health communities could be effective interventions for smoking cessation. This study aims to explore the reason why smokers turn to online health communities to support their smoking cessation from the social support perspective. We conducted a qualitative study by interviewing seven users of an online smoking cessation community in Finland. Our findings uncover that emotional support, informational support, and companionship are strong motivators for smokers to use smoking cessation online communities. Further, informational support and companionship are found to have different importance for people at different stages of smoking cessation. The role of companionship also varies between posters and lurkers of smoking cessation online community. The findings in this research provide practical guidelines to smoking cessation online health communities on how to understand smokers’ needs and retain them to use smoking cessation online health communities from the social support perspective, aiming to support their smoking cessation.
Proceedings of the 2019 Pacific Asia Conference on Information Systems (PACIS)